Day-care management of severe and very severe pneumonia, without associated co-morbidities such as severe malnutrition, in an urban health clinic in Dhaka, Bangladesh. Issue 6 (5th September 2007) - Ashraf, H; Jahan, S A; Alam, N H; Mahmud, R; Kamal, S M; Salam, M A; Gyr, N
Abstract : Background: Management of severe and very severe pneumonia in children relies on hospital-based treatment, but practical barriers often prevent children in areas with the highest rates from receiving hospital care. Objective: To develop and prospectively evaluate a day-care clinic approach, which provided antibiotics, feeding and supportive care during the day with continued care provided by parents at home, as an effective alternative to hospitalisation. Methods: Children aged 2–59 months with severe or very severe pneumonia without associated co-morbidities, denied admission to hospital because of lack of beds, were enrolled at Radda Clinic, Dhaka and received antibiotics, feeding and supportive care from 08:00 to 17:00 every day, while mothers were educated on continuation of care at home during the night. Results: From June 2003 to May 2005, 251 children were enrolled. Severe and very severe pneumonia was present in 189 (75%) and 62 (25%) children, respectively, and 143 (57%) were hypoxaemic with a mean (SD) oxygen saturation of 93 (4)%, which increased to 98 (3)% on oxygen therapy. The mean (SD) day-care period was 7 (2) days. Successful management was possible in 234 children (93% (95% CI 89% to 96%)), but 11 (4.4% (95% CI 2.5% to 7.7%)) had to be referred to hospital, and six (2.4% (95% CI 1.1% to 5.1%)) discontinued treatment. There were no deaths during the day-care study period; however, four children (1.6% (95% CI 0.6% to 4.0%)) died during the 3-month follow-up period, and 11 (4.4% (95% CI 2.5% to 7.7%)) required hospital admission. Conclusion: Severe and very severe pneumonia in children without associated co-morbidities such as severe malnutrition can be successfully managed at day-care clinics.